1H NMR metabolic profiling for the differentiation of fish species - Melike Saglam; Nele Paasch; Anna Lena Horns; Markus Weidner; René Bachmann (Food Chemistry Advances, 2024)
The determination of fish species is an important task for food control, especially in the case of very similar and processed fish or fish products. Typically, this analysis is carried out by DNA-based methods. We show that using a simple extraction and analysis of the 1H NMR spectra of these extracts a fast discrimination of fish species is possible. For this purpose, 69 samples consisting of five sample groups (iridescent shark, European plaice, rock sole, witch flounder and common sole) were analysed. The large differences in the 1H spectra could be further highlighted with a principal component analysis and led to a graphical differentiation of most sample groups. The identification of relevant metabolites shows high variability in the osmolyte profile of the analysed fishes, as well as high arsenobetaine concentrations in witch flounders and common soles. A classification of the samples was performed using a subspace discriminant algorithm resulting in a recognition rate of 100 % for all samples, regardless of additives like citric acid or lysine. These results show that 1H NMR spectroscopy is a robust, simple and rapid method for the recognition of the fish species studied.